Natacha Rambova papers - Rambova, Natacha
Typewritten monographs and notes, together with prints and photographs, reflecting Rambova's research in Egyptology and cosmology under the auspices of the Bollingen Foundation. Some material relates to Greek mythology.
Actress, cinematic designer, and spiritualist. Formerly known as Winifred Shaughnessy Hudnut. Married Rudolph Valentino. Born 1897, died 1966.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bollingen Foundation; Cosmology; Egyptology; Mythology, Greek; Actresses; Set designers; Spiritualists